2010
DOI: 10.1111/j.1439-0507.2009.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation of 24- vs. 48-h itraconazole minimum inhibitory concentrations with microbiological and survival outcomes in a guinea pig model of disseminated candidiasis

Abstract: A 'trailing' effect has been commonly observed when azole antifungals are tested against Candida spp. Previous experience with fluconazole indicates that 24-h minimum inhibitory concentration (MIC) values are more compatible endpoints when compared with clinical outcomes. We evaluated the trailing effect of Candida isolates tested with itraconazole in a guinea pig model of systemic candidiasis. Survival and organ burden were only significantly affected by using a higher dose of itraconazole, irrespective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The information regarding the in vivo relevance of TE is scarce. Some studies suggest that there is no correlation between the adaptation mechanism and the efficacy of fluconazole or itraconazole in animal models [23,24]. We investigated if there was any correlation between the presence of these effects and the clinical outcome of the infected patients and showed that in subjects treated with azoles before the isolation of the yeast through blood sampling, TE was present in fewer strains.…”
Section: Discussionmentioning
confidence: 99%
“…The information regarding the in vivo relevance of TE is scarce. Some studies suggest that there is no correlation between the adaptation mechanism and the efficacy of fluconazole or itraconazole in animal models [23,24]. We investigated if there was any correlation between the presence of these effects and the clinical outcome of the infected patients and showed that in subjects treated with azoles before the isolation of the yeast through blood sampling, TE was present in fewer strains.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies found that C. albicans isolates with strong trailing to fluconazole have the same mutations in ERG11 and up-regulation of efflux pumps as resistant strains [12]. This similar resistance adaptation would suggest that isolates lead to similar therapeutic failures for azole drugs as resistant isolates, however the in vivo murine models suggest that isolates that exhibit trailing respond to azole therapy, which is contractionary [54,55,56,57]. Patient data also suggest that trailing does not confer any advantage to the fungus during the exposure to antifungals in patients.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to evaluate if we can generate a predictive correlation of in vitro and in vivo results by the use of G. mellonella larvae for echinocandins and since no correlation was shown in murine models [11]. As the efficacy of azole therapy in murine models and Candida isolates was widely demonstrated in particular for fluconazole [54,55,56,57]; we aimed to investigate the impact of trailing for voriconazole and C. albicans .…”
Section: Methodsmentioning
confidence: 99%